Planejamento patrimonial e sucessório: os arranjos jurídicos utilizados pelas empresas familiares rurais - Iserhardt, Patrícia Machado (2023)
Although the literature confirms the need to carry out estate and succession planning, and knows the reasons why young people do not remain in the countryside, generational succession is researched far from hereditary succession, and legal strategies aimed at rural family businesses are not studied. The migration of young people has a direct impact on succession processes, as well as the end of rural family businesses, due to conflicts over succession. The objective of this study is to identify the succession planning strategies used by medium and large rural family businesses, in the municipality of Júlio de Castilhos, Rio Grande do Sul, from the perspective of legal arrangements. The theoretical approach that will be followed for this discussion was carried out by Pierre Bourdieu, who brings the project cultivated by the family to be perpetuated for the next generations as the conatus, which is not only a project of a physical, material and objective nature, it also contemplates the values, beliefs, feelings and emotions involved in the project developed by the parents, that is, in addition to inheritance, the legacy, brings the notion of habitus as a system of unconscious dispositions that is the result of the imposition of structures of society and the environment in which they live. Furthermore, the analysis regarding the Three Circle Model, created by Tagiuri and Davis. The research approach is qualitative and explanatory, characterized as field research, with face-to-face interviews with managers of rural family businesses. The results were analyzed through content analysis, treatment of empirical and documentary material. The results showed that rural families are not properly organized as companies, no matter how much the legislation considers them so. Succession plans are informal, with the exception of a small portion of interviewees, in the percentage of 10% who have a rural family holding, a duly regularized company, consultancies for the implementation of legal arrangements and family governance, that is, families that have managed to organize hereditary succession and generational, while the founders are alive. It is essential to have financial, commercial, communication and human resources skills. There is an immense need to discuss succession in Brazilian agribusiness, uniting themes of great importance such as generational succession being planned together with hereditary succession, that is, with patrimonial and succession planning, through legal legal strategies for organizing assets, anticipating to the rules of hereditary succession and facilitating the introduction of generational succession. It is believed that the biggest challenge is the formulation of public policies, such as international actions, that encourage succession in rural family businesses.